A genetic variant (COMT) coding dopaminergic activity predicts personality traits in healthy elderly. (August 2015) - Kotyuk, Eszter; Duchek, Janet; Head, Denise; Szekely, Anna; Goate, Alison M.; Balota, David A.
Highlights: We examined associations of COMT rs4680 and personality in older adults. The COMT rs4680 GG genotype associated with lower Neuroticism scores. GG genotype also associated with higher Agreeableness and Conscientiousness scores. GG's dopamine release might be optimal for a more adaptive personality profile. Abstract: Association studies between the NEO five factor personality inventory and COMT rs4680 have focused on young adults and the results have been inconsistent. However, personality and cortical changes with age may put older adults in a more sensitive range for detecting a relationship. The present study examined associations of COMT rs4680 and personality in older adults. Genetic association analyses were carried out between the NEO and the targeted COMT rs4680 in a large, well-characterized sample of healthy, cognitively normal older adults ( N = 616, mean age = 69.26 years). Three significant associations were found: participants with GG genotype showed lower mean scores on Neuroticism ( p = 0.039) and higher scores on Agreeableness ( p = 0.020) and Conscientiousness ( p = 0.006) than participants with AA or AG genotypes. These results suggest that older adults with higher COMT enzymatic activity (GG), therefore lower dopamine level, have lower Neuroticism scores, and higher Agreeableness and Conscientiousness scores. This is consistent with a recent model of phasic and tonic dopamine release suggesting that even though GG genotype is associated with lower tonic dopamine release, the phasic release of dopamine might be optimal for a more adaptive personality profile.